2020
DOI: 10.1177/1591019920949094
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic intracranial hypertension with stenosis of a solitary occipital venous sinus treated with stenting

Abstract: A 47-year-old live kidney-donor woman presented with headaches and blurred vision. Neuro-ophthalmological examination demonstrated papilledema and right eye inferior nasal defect. Brain MRV showed no sinus thrombosis but solitary right venous sinus draining the torcular Herophili to right jugular bulb. Lumbar puncture revealed elevated CSF opening pressure of 40 cm H2O with normal composition. She was diagnosed with idiopathic intracranial hypertension (IIH). She did not tolerate medical management and decline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Following an extensive systematic review, our patient's gradient pressure surpasses all others documented in the literature (Table). 3-52 According to our systematic review, the highest recorded gradient pressure was 67 mm Hg reported by Tschoe et al 36 who highlighted the impact of changes in mean arterial pressure and end-tidal carbon dioxide on venous sinus pressures in patients with IIH undergoing venous sinus stenting. Moreover, Ahmed et al reviewed clinical, venographic, and intracranial pressure data before and after stent placement in transverse sinus stenosis in 52 patients with IIH; the highest pressure gradient they reported was 41 mm Hg.…”
Section: Discussionmentioning
confidence: 82%
“…Following an extensive systematic review, our patient's gradient pressure surpasses all others documented in the literature (Table). 3-52 According to our systematic review, the highest recorded gradient pressure was 67 mm Hg reported by Tschoe et al 36 who highlighted the impact of changes in mean arterial pressure and end-tidal carbon dioxide on venous sinus pressures in patients with IIH undergoing venous sinus stenting. Moreover, Ahmed et al reviewed clinical, venographic, and intracranial pressure data before and after stent placement in transverse sinus stenosis in 52 patients with IIH; the highest pressure gradient they reported was 41 mm Hg.…”
Section: Discussionmentioning
confidence: 82%
“…9,20 Two recent case reports of MS stenosis associated with IIH described clinical improvement after stenting of the sinus, supporting LS and MS stenosis being similar pathologies. 13,14 Finally, 2 patients were treated for LS and MS stenoses during the same procedure, interpreted as a limitation of our results (because the responsibility of the MS stenosis is uncertain). However, performing 2 different interventions to test which stenosis was responsible for the PT was, in our opinion, not feasible outside a prospective clinical trial.…”
Section: Discussionmentioning
confidence: 95%
“…Preceding reports have described MS stenosis as a cause for venous PT 12 or IIH. 13,14 However, Li et al 12 referred to it as a stenosis of the vein of the hypoglossal canal. We believe it is an inaccurate name because the sinus is reaching the jugular bulb without crossing the hypoglossal canal.…”
Section: Discussionmentioning
confidence: 99%
“…In such cases, when IIH supervenes, stenosis along this pathway may occur. Al Balushi et al 103 published a case of IIH in which a persistent enlarged occipital sinus demonstrated severe distal stenosis, with hypoplastic right and aplastic left transverse sinuses. Stenting of the stenotic segment resulted in the resolution of papilledema and normalization of ICP.…”
Section: Stenosis Within Variant Venous Outflowmentioning
confidence: 99%